2012
DOI: 10.1007/s00167-011-1863-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical grading of the pivot shift test correlates best with tibial acceleration

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Ahldén et al 22 discovered in vitro a moderate correlation (r=0.58) between the PS clinical grading and the maximal acceleration of the tibia. Kopf et al 23 found a significant in-vivo difference between the healthy and injured knees but found no correlation to the PS clinical grading.…”
Section: Discussionmentioning
confidence: 98%
“…Ahldén et al 22 discovered in vitro a moderate correlation (r=0.58) between the PS clinical grading and the maximal acceleration of the tibia. Kopf et al 23 found a significant in-vivo difference between the healthy and injured knees but found no correlation to the PS clinical grading.…”
Section: Discussionmentioning
confidence: 98%
“…[34][35][36][37] In addition, tibial acceleration parameters have had good correlation with clinical grading of the pivot-shift test. [38][39][40] Limitations…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of bone bruise patterns can also provide insight into injury mechanisms. 20 The patient should also undergo quantitative pivot shift testing to assess for the degree of rotatory instability (Figure 1), 53, 54 which can indicate additional injury including clinically relevant meniscal tears, anterolateral complex injuries, or underlying bony morphology consistent with rotatory instability. In these cases, additional procedures such as extra-articular tenodesis may be indicated.…”
Section: Technical Considerations For Revision Acl Reconstruction Surmentioning
confidence: 99%